Buruli ulcer: A review of In Vitro tests to screen natural products for activity against Mycobacterium ulcerans - YEMOA, Loconon Y. Achille; GBENOU, Joachim; AFFOLABI, DISSOU; MANSOUROU, Moudachirou; BIGOT, KOFFI ANDRÉ; ANAGONOU-YEHOUENOU, SEVERIN (My University, 2011)
Buruli ulcer (BU), caused by Mycobacterium ulcerans, has recently been recognized by the World Health Organization (WHO) as an important emerging disease. It is largely a problem of the poor in remote rural areas and has emerged as an important cause of human suffering. While antimycobacterial therapy is often effective for the earliest nodular or ulcerative lesions, for advanced ulcerated lesions, surgery is sometimes necessary. Antimycobacterial drugs may also prevent relapses or disseminated infections. Efficient alternatives different from surgery are presently explored because this treatment deals with huge restrictive factors such as the necessity of prolonged hospitalization, its high cost, and the scars after surgery. Traditional treatment remains the first option for poor populations of remote areas who may have problems of accessibility to synthetic products because of their high cost. The search for efficient natural products active on M. ulcerans should then be encouraged because they are part of the natural heritage of these populations; they are affordable financially and can be used at the earliest stage. This review provides a number of tests that will help to evaluate the antimycobacterial activity of natural products against M. ulcerans, which are adapted to its slow growing rate, and lists active extracts published up to now in Medline.
Keywords: natural products; antimycobacterial; screening; Buruli ulcer